(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the Mutagenicity of Metformin and Aspartame in vitro. Study Design: Observational / Analytical study Place and Duration of Study; This study was carried out at Department of Pharmacology and Toxicology, University of Veterinary and Animal Sciences Lahore from 1st Jan 2011 to Dec 2011. Materials and Methods: Ames Salmonella/ Microsome Mutagenicity Assay was used to check the mutagenic potential of test chemicals & control. The data was analyzed by using Statistical Package of Social Sciences. Results: Metformin was found to be highly mutagenic against TA100 and TA98 both in the presence and absence of metabolic activation system. The results were significant because there was 2 fold rise in number of revertants as compared to the negative control. Overall metformin exhibited more mutagenicity against TA 100 as compared to TA 98 strain of Salmonella Typhimurium. Aspartame showed significant rise in mutagenicity at 100µg/plate and 250µg/plate in dose dependant manner against TA 100 in presence of metabolic activation system. When combination doses of aspartame and metformin were studied, even those doses became mutagenic which were not mutagenic alone. The data advocates that combination doses showed significant additive effect (p < 0.05) in the intensity of mutagenic index as compared to the mutagenic index of metformin and aspartame alone. Conclusion: Both of these products alone & together may cause significant damage to the cells of body as well. Combination therapy of these products should be monitored closely.